Possible functional roles of patellamides in the ascidian-prochloron symbiosis - Baur, Philipp; Kühl, Michael; Comba, Peter; Behrendt, Lars (Marine drugs, 2022)
Patellamides are highly bioactive compounds found along with other cyanobactins in the symbiosis between didemnid ascidians and the enigmatic cyanobacterium Prochloron. The biosynthetic pathway of patellamide synthesis is well understood, the relevant operons have been identified in the Prochloron genome and genes involved in patellamide synthesis are among the most highly transcribed cyanobacterial genes in hospite. However, a more detailed study of the in vivo dynamics of patellamides and their function in the ascidian-Prochloron symbiosis is complicated by the fact that Prochloron remains uncultivated despite numerous attempts since its discovery in 1975. A major challenge is to account for the highly dynamic microenvironmental conditions experienced by Prochloron in hospite, where light-dark cycles drive rapid shifts between hyperoxia and anoxia as well as pH variations from pH ~6 to ~10. Recently, work on patellamide analogues has pointed out a range of different catalytic functions of patellamide that could prove essential for the ascidian-Prochloron symbiosis and could be modulated by the strong microenvironmental dynamics. Here, we review fundamental properties of patellamides and their occurrence and dynamics in vitro and in vivo. We discuss possible functions of patellamides in the ascidian-Prochloron symbiosis and identify important knowledge gaps and needs for further experimental studies.
Gesehen am 13.04.2022